THE EFFECT OF USING SIMILE GAMES TECHNIQUE TO INCREASE STUDENTS’ VOCABULARY MASTERY AT THE EIGHTH GRADE STUDENTS OF SMP SWASTA BPI PALUH KURAU - Enni Maisaroh; Micha Flora Br. Siregar (Journal MELT (Medium for English Language Teaching), 2022)
This Study was aimed to find the significance of The Effect of Using Smile Games to Increase Students’  Vocabulary Mastery. This research used experimental design.This research was conducted at the SMP Swasta BPI Paluh Kurau. The population of this research is the students of class VIII SMA. The sample of this study consisted of 54 students, namely 27 students in the experimental class and 27 students in the control class. The experimental class was taught using simile games technique while the control class used conventional methods. The results of this research show that the mean score in the experimental class using simile games tehnique was (85,74). In the control class using conventional methods showed that the mean was (69,26). So, the results of the experimental class are higher than the control class. The score of tobs (7.578) is higher than t_table (2.007) at a significance level of 0.05 in the two-tailed test. That is, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. So from this study it was found that there was a significant effect of using simile games techniqueto increase students’ vocabulary mastery